Early use of peripherally inserted central catheters is safe in Staphylococcus aureus bacteraemia. Issue 1 (3rd January 2018) - Stewart, James D.; Runnegar, Naomi
Abstract: Background: Management of Staphylococcus aureus bacteraemia (SAB) includes prolonged intravenous antibiotics often administered through a peripherally inserted central catheter (PICC). Optimal timing of PICC insertion for SAB treatment is unknown. There are concerns that early insertion may increase the risk of subsequent line infection. Aims: This retrospective audit aims to determine if early PICC insertion is safe. The outcomes considered included crude mortality, attributable mortality, PICC line infections, duration of bacteraemia and relapsed SAB. Methods: Patients with SAB at our institution between March 2013 and September 2016 were identified. Early PICC line insertion was defined as occurring within 48 h of index positive blood culture. Results: This retrospective audit identified 357 patients with SAB who subsequently received a PICC. This study did not show any significant differences between the early and late PICC insertion groups for attributable mortality (6.3% and 4.8%, P = 0.27), duration of bacteraemia (median 2 days for both groups, P = 0.48) and relapsed SAB (4.7% and 4.1%, P = 0.74). Importantly, no confirmed PICC infections were identified in either group. Conclusions: Early PICC insertion in SAB appears safe in this retrospective audit. If validated in prospective studies, this should allow for the early establishment of safe, reliable intraveous access in SAB patients.